Extended dual antiplatelet therapy with ticagrelor 60 mg in patients with prior myocardial infarction: The design of ALETHEIA, a multi‐country observational study. Issue 10 (8th August 2021) - Lesén, Eva; Hewitt, Christopher; Giannitsis, Evangelos; Hedberg, Jonatan; Jernberg, Tomas; Lambrelli, Dimitra; Maggioni, Aldo P.; Simeone, Jason C.; Ariza‐Solé, Albert; Storey, Robert F.; ten Berg, Jurrien; Bonaca, Marc; et al.
Abstract: Introduction: Clinical guidelines recommend extended treatment with dual antiplatelet therapy (DAPT) with ticagrelor 60 mg (twice daily) beyond 12 months in high‐risk patients with a history of myocardial infarction (MI) who have previously tolerated DAPT and are not at heightened bleeding risk. However, evidence on patterns of use and associated clinical outcomes in routine clinical practice is limited. Methods: ALETHEIA is an observational, multi‐country study, designed to describe characteristics, treatment persistence, and bleeding and cardiovascular (CV) outcomes in post‐MI patients who initiate ticagrelor 60 mg in routine clinical practice (NCT04568083). The study will include electronic health data in the United States (US; Medicare, commercial claims) and Europe (Sweden, Italy, United Kingdom, Germany). Characteristics will be described among patients with and without ticagrelor 60 mg ≥1 year post‐MI. Assuming an a priori threshold of 5000 person‐years on‐treatment is met, to ensure sufficient precision, clinical outcomes (bleeding and CV events) among patients treated with ticagrelor 60 mg will be assessed. Risk factors for clinical outcomes and treatment discontinuation will be assessed in patients with ticagrelor 60 mg and meta‐analysis used to combine estimates across databases. Cohort selection will initiate from the ticagrelor 60 mg US and European approval dates and end February 2020. An estimated total of 7250 patients prescribed ticagrelor 60 mg are expected to be included. Discussion: An increased understanding of patterns of ticagrelor 60 mg use and associated clinical outcomes among high‐risk patients with a prior MI is needed. The a priori specified stepwise approach adapted in this observational study is expected to generate useful evidence for clinical decision‐making and treatment optimization.